Unpacking the Challenges of Credit Point Policy Implementation for Academic Promotion in Nusa Cendana University (2022–2024) - Karuniawati Steven, Mitha; Putu Yoga Bumi Pradana, I; Salim Adang Djaha, Ajis (Jurnal Ilmu Administrasi Negara AsIAN (Asosiasi Ilmuwan Administrasi Negara), 2025)
The credit point policy for lecturers plays a central role in academic promotion within higher education. However, its implementation often faces multiple challenges, particularly in institutions with limited administrative and digital capacities. This study specifically aims to examine the policy content and implementation context of the credit point system at Nusa Cendana University during 2022–2024, with a focus on identifying the key barriers and enablers shaping academic promotion outcomes. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis involving 15 key informants, including university leaders, faculty administrators, and lecturers. Findings reveal that although the policy is formally grounded in national regulations, its practical application is hindered by limited policy literacy, complex procedural requirements, unequal workload distribution, insufficient technical assistance, and weak institutional support. These barriers have led to ineffective promotion outcomes and underutilization of the policy’s potential. To address these challenges, the study recommends simplifying technical guidelines, enhancing institutional coordination, accelerating administrative digitalization, and fostering a supportive academic ecosystem. A web-based information system is also proposed to assist lecturers in calculating and managing credit points more efficiently. By applying Grindle’s policy implementation framework, this research contributes to the literature on higher education governance by demonstrating how national-level regulatory instruments are mediated by institutional capacity and local contextual realities, particularly in resource-constrained universities in peripheral regions of Indonesia.